Estruturação da comunidade zooplanctônica em um conjunto de veredas na região Neotropical: abordagem mecanicista e elementos de estrutura de metacomunidades. - Pedroso, Clemerson Richard (2019)
Veredas environments are great models for the study of how the distribution and structuring of the communities occurs, because they have isolated and distant pools, allowing the formation of a gradient. Studies of metacommunities have a great importance for ecological knowledge and formulation of strategies for conservation and restoration of degraded environments. In this context, the objective of the present study is to investigate the main of assembly mechanisms responsible for the structuring of the zooplankton community in a complex of neotropical veredas. Zooplankton were sampled in the pelagic region of 15 veredas in April 2018. The zooplankton of these environments had a distribution influenced by spatial and environmental factors. The total zooplankton community had environmental and spatial influence. For rotifers the relative importance of environmental factors was greater while cladocerans and copepods were more structured by space. The community was still structured according to the Gleasonian model of distribution, with some peculiarities among the groups, where rotifers had Gleasonian structure, cladocerans had Quasi-Gleasonian and copepods Quasi-Nested Random. The influence of environmental and spatial factors and the resulting structure of the zooplankton metacommunity seem to be directly related to the dispersal capacity of the species. Differences in relative importance of the factors that shaped the community highlight the idiosyncratic characteristics of zooplankton species. Thus, we emphasize the importance of using the two approaches of metacommunity studies, generating better results, which can help in conservation and restoration.